Antithrombotic Adherence to guideline-directed therapy and risk profile among Non-Valvular Atrial fibrillation patients - Sherpa, Kunjang; Adhikari, Chandra Mani; Prajapati, Dipanker; Manandhar, Reeju; Adhikari, Nripesh; Raut, Roshan; Dhungana, Murari; Bajracharya, Prashant; Joshi, Surakshya; Timilsena, Birat K; Bogati, Amrit; Yadav, Santosh; et al. (Nepalese Heart Journal, 2023)
Introduction: Patients with Atrial fbrillation (AF) are at fivefold higher risk for Ischemic stroke than in the general population. Although the current therapeutic guidelines recommend the use of anticoagulants for thromboembolic prophylaxis in patients with nonvalvular AF (NVAF) with additional risk factor(s) for stroke, the global registry data show non-adherence to guidelines for the management of stroke in diferent regions of the world. The current study conducted at the tertiary referral cardiac center of Nepal for addressing the risk profle of stroke based on the current risk scores and the use of antithrombotic agents NVAF patients. Methodology: This was a descriptive observational cross sectional study conducted at Shahid Gangalal National Heart Centre (SGNHC), Kathmandu, Nepal from December 2020 to June 2020 which included patients with Nonvalvular AF. The main objective of the study was to study the clinical characteristics, stroke risk profle based on CHA ₂DS₂-VaSc score and risk of bleeding based on HAS-BLED score and the patterns of use of antithrombotic agents in NVAF patients. Results: A total of 79 cases of NVAF were included with 48(60.8%) males and 31(39.2%) females. The mean CHA₂DS₂-VaSc and HAS-BLED score were 2.44±1.2 and 1.51±1.4 respectively. The majority patients 38% had permanent AF followed by 25.5% had paroxysmal AF. Majority of patients were symptomatic with 67.1% presented with palpitation while 32.9% presented with shortness of breath (SOB). Based on the European Heart Rhythm Association (EHRA) AF related symptoms score, 41.8% had EHRA 2a and 2b while 1.3% had EHRA 4 score. The use of anticoagulants in patients with Nonvalvular AF was 41.6%, with NOACS in 33 % and warfarin used in 8.9% cases. The majority of patients 51.8% of study population were using anti-platelet agents with aspirin in 49.3 % and clopidogrel in 2.5 % cases while no medication in 6.3% of cases. Although 70.8% patients had CHA₂DS₂-VaSc score of 2 or more but the use of anticoagulants was only 58.9% with 46.4% NOACS and 12.5% using warfarin among this group of patients. Conclusion: Although the use of anticoagulant with NOACS in patients with higher risk of stroke is increasing, it is still underused in the majority of cases .There is a need of nationwide AF registry and the need of adoption of the current recommended guidelines to increase use of Anticoagulants in patients with Nonvalvular AF patients for the prevention of stroke .